Effectiveness of Jamula in Lamongan: A Qualitative Policy Evaluation - NURROCHIM, Raihan Wahyu (PT Keberlanjutan Strategis Indonesia, 2025)
This study evaluates the effectiveness of the JAMULA (Jalan Mantap dan Alus Lamongan) Program as a regional public policy aimed at improving road infrastructure and mobility in Lamongan Regency. Guided by the question of how effectively JAMULA has been implemented, the research applies Sutrisno’s five indicators, program understanding, target accuracy, timeliness, goal attainment, and tangible change, to assess both processes and outcomes. A qualitative descriptive design was employed, drawing on non-participant observation at the Public Works and Highways Office and selected road segments, semi-structured interviews with eleven informants (policy makers, implementers, and residents from beneficiary and non-beneficiary areas), and document analysis for triangulation. Findings indicate that program understanding is strong due to sustained communication and participatory planning; targeting aligns with the Regional Government Work Plan and economic corridors; implementation meets timeliness through disciplined scheduling; goals are largely attained, reflected in improved road conditions and user satisfaction; and tangible changes include safer, more reliable travel and expanded market access for local MSMEs. Constraints persist in the form of limited regional budgets and uneven territorial reach, which necessitate phased implementation and financing innovation. Overall, JAMULA demonstrates substantive effectiveness while underscoring the need for broadened coverage, strengthened post-construction assurance, and diversified funding to sustain “jalan mantap” across the regency.